Potential of Beauveria bassiana Controlling Nilaparvata lugens for Food Security: A Review Article - Fathurohman, Fijar Muhamad; Parsa, Raisa Shakila; Lestari, Indah; Falihah, Farica; Soesanto, Loekas (Jurnal Biologi Tropis, 2026)
The Brown Planthopper (Nilaparvata lugens Stål) is a strategic pest threatening the stability of national rice production. Farmers' dependence on synthetic insecticides has triggered pest resistance and environmental degradation, making the utilization of biological agents such as the entomopathogenic fungus Beauveria bassiana an urgent alternative solution. This study aims to comprehensively analyze the potential, mechanisms, and effectiveness of B. bassiana in controlling N. lugens. The method used is a Systematic Literature Review (SLR) by examining experimental articles from accredited national journals and reputable international journals published between 2018 and 2025. Results of data synthesis indicate that B. bassiana has a very high level of pathogenicity (nymph mortality >78%), especially when using local isolates cultured on corn media. However, its effectiveness is highly influenced by abiotic factors, where conidial viability is optimal at 25°C and drops sharply at extreme temperatures (34°C). Recent findings prove that B. bassiana can colonize as an endophyte within rice tissues, suppressing planthopper fecundity while simultaneously inducing systemic plant resistance. Additionally, this fungus is proven compatible and synergistic when combined with sublethal insecticide doses. It is concluded that B. bassiana is effective as both a contact biopesticide and an internal protection agent within Integrated Pest Management.